Whistleblowing judgment as mediator to the influence of whistleblowing intention in universities - Kristine Belaja, Intan Salwani Mohamed (Opción, 2019)
Based on the Theory of Reasoned Action as its underlying theory, the present study attempts to investigate the role of whistleblowing judgment as a mediating factor to the influence of whistleblowing intentions among the tested factors. Findings from the study showed that whistleblowing judgment only has a mediating effect towards relativism and idealism in influencing whistleblowing intention. In conclusion, ethics training can aid individuals to make ethical choices when met with ethical dilemmas.